Determinants of Retail Customer Satisfaction-A Study of Organized Retail Outlets in Kurukshetra - Malik, Manju Rani (Indian Journal of Marketing, 2011)
Dynamic changes in the field of retailing during the last decade have promoted a focus on "service" to the customer. Customer satisfaction has drawn the attention of the researcher and managers in recent decades. With the rapid development of modern organized retailers in Kurukshetra in terms of number of stores and value, understanding of retail customer satisfaction and identifying determinants of retail customer satisfaction has become of strategic importance for organized retailers or the so-called organized retail outlets in Kurukshetra, Haryana. The main purpose of this study is to explore the relationship among the customer satisfaction and different dimensions of service quality i.e. Product characteristics, price factor, physical aspects, promotional schemes and personnel interaction, and identify the most influencing factors that motivate the customers to visit the organized retail outlets. The analysis is based upon organized retail outlets intercept survey with 150 respondents across a range of demographics. In assessing service quality of organized retail outlets, a questionnaire developed after borrowing an idea from the framework developed by Dalbolar et. Al (1996) and Reid and Gundlach (1984). Statistical tools used are frequency counts, percentage and chi-square test, set at a .02 level of significance. The results indicate that variety of products, branded products and availability of necessary goods under same roof, reasonable price and fixed price and location of organized retail outlets at close to residence or work place play a significant role in motivating the customers to visit organized retail outlets. There is a significant relationship between customer satisfaction and the 5 dimensions of service quality of organized retail outlets; Product Characteristics, Price factor, Physical aspects, Promotional schemes and Personnel interaction. Since the results of the study show that customers' satisfaction is related with service quality of retail stores in terms of the above said 5 dimensions, therefore, retailers need to stress on these related aspects in providing their services.